2003
DOI: 10.1016/s0002-9440(10)63507-9
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biological Activity for Galectin-1

Abstract: Galectin-1 (Gal-1), the prototype of a family of ␤-galactoside-binding proteins, has been shown to attenuate experimental acute and chronic inflammation. In view of the fact that endothelial cells (ECs), but not human polymorphonuclear leukocytes (PMNs), expressed Gal-1 we tested here the hypothesis that the protein could modulate leukocyte-EC interaction in inflammatory settings. In vitro, human recombinant (hr) Gal-1 inhibited PMN chemotaxis and trans-endothelial migration. These actions were specific as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(51 citation statements)
references
References 44 publications
1
33
0
3
Order By: Relevance
“…Galectins have been shown to be able to contribute to regulation of the migration of immune cells. Human recombinant galectin-1 was found to inhibit chemotaxis as well as trans-endothelial migration of PMN in vitro and inhibit interleukin-1β-induced PMN recruitment into the mouse peritoneal cavity [128]. Intravital microscopy analysis demonstrated that it suppresses the leukocyte flux, but not their rolling velocity [128].…”
Section: Regulation Of the Functions Of Immune Cellsmentioning
confidence: 99%
“…Galectins have been shown to be able to contribute to regulation of the migration of immune cells. Human recombinant galectin-1 was found to inhibit chemotaxis as well as trans-endothelial migration of PMN in vitro and inhibit interleukin-1β-induced PMN recruitment into the mouse peritoneal cavity [128]. Intravital microscopy analysis demonstrated that it suppresses the leukocyte flux, but not their rolling velocity [128].…”
Section: Regulation Of the Functions Of Immune Cellsmentioning
confidence: 99%
“…However, in adults, it is produced by a majority of tissues (8, 48 -50). In the vasculature, Gal-1 is produced by SMC and endothelial cells and is regulated by proinflammatory mediators and cell activation, including changes in vascular cells that allow them to participate in the immune response (10,30,51). In vitro, Gal-1 regulates SMC attachment to laminin and fibronectin in a dose-dependent manner, which subsequently regulates proliferation, migration, adhesion, and spreading of SMCs by means of ␤ 1 -integrins and focal adhesion kinase signaling (8,9,10,23,37,44).…”
mentioning
confidence: 99%
“…Such a sensor may be important in dictating the distribution and longevity of Gal-1 signaling. For example, whereas Gal-1 induces turnover of neutrophils (3,6,40), inhibits leukocyte chemotaxis and induces immunosuppressive cytokine secretion in both naive and activated T cells (40,61), premature engagement of infiltrating leukocyte by Gal-1 could ameliorate an otherwise productive and necessary inflammatory response. The highly oxidative environment surrounding inflammation likely facilitates the oxidation of Gal-1 released during primary tissue injury prior to significant leukocyte recruitment (1), allowing leukocytes to successfully neutralize pathogen or remove necrotic tissue without being impeded by the immunosuppressive effects of Gal-1.…”
Section: Discussionmentioning
confidence: 99%